2022
DOI: 10.1007/s10552-022-01578-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to colorectal cancer screening in Ghana: a qualitative study of patients and physicians

Abstract: Purpose The incidence of colorectal cancer (CRC) in Ghana has increased eightfold since the 1960s. In 2011, national guidelines were set forth recommending all patients aged 50–70 years old undergo annual CRC screening with fecal occult blood testing (FOBT), but adherence to these guidelines is poor and screening rates remain low for unclear reasons. Methods We performed semi-structured interviews with 28 Ghanaians including physicians ( n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[#], location, and article type/study design Sample size Barriers Recommendations [ 20 ]; Kenya; perspectives paper Systematic: limited endoscopic capabilities (training, infrastructure), limited no. of trained pathologists (turnaround time, 2–6 weeks) Train nonphysician endoscopists; use high-resolution micro-endoscopy to improve detection of neoplasia; expand insurance coverage [ 18 ]; Africa; editorial Systematic: infrastructure, provider availability, cost of screening procedure; Patient: acceptance of screening; Provider: pathologic services, endoscopic training Consider FIT for CRC screening; consider flexible sigmoidoscopy or serologic blood tests; in-person and virtual training from other specialties and nonphysician providers to increase endoscopic capacity by health care professionals and endoscopic equipment manufacturers [ 16 ]; Egypt; qualitative study, 1-h semi-structured interview 17 physicians (8 specialists, 9 primary care) Systematic: lack of test availability, cost of screening procedure; Patient: Socio-economic status, fear, cost, cultural belief (only see doctor when symptomatic); Provider: lack of emphasis on prevention, belief that only high-risk patients should be screened, lack of confidence to perform and interpret test, inadequate training for lab technicians and providers Implement a media campaign emphasising early detection, curability, and prevention; educate physicians and elicit physical engagement; make screening tests widely available; provide well-trained providers; lower cost [ 12 ]; Ghana; qualitative study 39 physicians Systematic: lack of equipment/facilities, high screening costs/lack of insurance coverage; Patient: lack awareness of early screening benefits, not perceiving CRC as a serious health threat, poor adherence; Provider: not recommending CRC screening for asymptomatic average-risk patients, lack of training/personal adherence to screening Government to make sustained commitment and financial investment for CRC screening; further studies on true incidence of CRC and individual and societal cost of CRC screening to motivate stake holders to support CRC prevention on a national scale; further studies to understand the exact beliefs and level of knowledge held by the Ghanaian population [ 17 ]; Ghana; qualitative study, interview to understand factors driving screening adherence 14 patients, 14 physicians Systematic: access to healthcare, lack of national prioritisation; Patient: sociocultural factors, reliance on alternative medicine/religion, perception of stool co...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[#], location, and article type/study design Sample size Barriers Recommendations [ 20 ]; Kenya; perspectives paper Systematic: limited endoscopic capabilities (training, infrastructure), limited no. of trained pathologists (turnaround time, 2–6 weeks) Train nonphysician endoscopists; use high-resolution micro-endoscopy to improve detection of neoplasia; expand insurance coverage [ 18 ]; Africa; editorial Systematic: infrastructure, provider availability, cost of screening procedure; Patient: acceptance of screening; Provider: pathologic services, endoscopic training Consider FIT for CRC screening; consider flexible sigmoidoscopy or serologic blood tests; in-person and virtual training from other specialties and nonphysician providers to increase endoscopic capacity by health care professionals and endoscopic equipment manufacturers [ 16 ]; Egypt; qualitative study, 1-h semi-structured interview 17 physicians (8 specialists, 9 primary care) Systematic: lack of test availability, cost of screening procedure; Patient: Socio-economic status, fear, cost, cultural belief (only see doctor when symptomatic); Provider: lack of emphasis on prevention, belief that only high-risk patients should be screened, lack of confidence to perform and interpret test, inadequate training for lab technicians and providers Implement a media campaign emphasising early detection, curability, and prevention; educate physicians and elicit physical engagement; make screening tests widely available; provide well-trained providers; lower cost [ 12 ]; Ghana; qualitative study 39 physicians Systematic: lack of equipment/facilities, high screening costs/lack of insurance coverage; Patient: lack awareness of early screening benefits, not perceiving CRC as a serious health threat, poor adherence; Provider: not recommending CRC screening for asymptomatic average-risk patients, lack of training/personal adherence to screening Government to make sustained commitment and financial investment for CRC screening; further studies on true incidence of CRC and individual and societal cost of CRC screening to motivate stake holders to support CRC prevention on a national scale; further studies to understand the exact beliefs and level of knowledge held by the Ghanaian population [ 17 ]; Ghana; qualitative study, interview to understand factors driving screening adherence 14 patients, 14 physicians Systematic: access to healthcare, lack of national prioritisation; Patient: sociocultural factors, reliance on alternative medicine/religion, perception of stool co...…”
Section: Resultsmentioning
confidence: 99%
“…Another barrier to CRC screening in Africa was the lack of patient knowledge [ 13 , 17 , 18 , 20 , 26 , 27 ]. Lussiez et al [ 13 ] reported that 86.2% of physicians interviewed in Ghana identified patients’ lack of awareness of screening, specifically patients not perceiving CRC as a serious health threat, as a barrier to CRC screening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like most SSA countries, Ghana lacks a national colostomy registry, however, institutional-based data indicate increasing incidence for colostomy due to recent increases in colorectal cancers and diverticular diseases [9]. For instance, recent data points to the fact that about 33 percent new cases of colorectal cancer out of every 100,000 persons are recorded yearly [10,11]. These statistical evidences indicate that the problem of colorectal cancers is no longer uncommon among the indigenous people of Ghana.…”
Section: Introductionmentioning
confidence: 99%